Implementasi model pembelajaran cooperative learning type jigsaw dalam rangka peningkatan motivasi dan prestasi pelajaran matematika pada siswa kelas VII MTsN Yogyakarta tahun pelajaran 2015/2016 - Sirojul Huda; Samsi Haryanto; Chaerun Chaerun (Universitas Sarjanawiyata Tamansiswa, 2017)
Model Pembelajaran Cooperative learning Tipe Jigsawdi kelas VIIMTsN Yogyakarta I Mlati Sleman tahun pelajaran 2015/2016SD bertujuan untuk meningkatkan motivasi dan prestasi belajar matematika materi bangun datar segi empat. Penelitian Tindakan Kelas dilakukan oleh peneliti sebagai guru kelas dan guru matematika kelas 9 sebagai observer. Penelitian dilaksanakan dalam dua siklus., subyek penelitian ini adalah siswa kelas VII semester II MTsN Yogyakarta I Mlati Sleman tahun pelajaran 2015/2016 berjumlah 33 siswa. Teknik analisis data digunakan analisis perbandingan,. Dari prosentase dideskripsikan kearah kecenderungan tindakan guru dan reaksi serta hasil belajar siswa.Prestasi belajar sebelum tindakan kelas rata-rata 69,58 ketuntasan individual sebanyak 22siswa(66,7%).Setelah tindakan kelas pada siklusI nilai rata-rata 73,75 dengan ketuntasan individual28siswa (84,84%), siklus II nilai rata-rata mencapai 77,33 dengan ketuntasan individual 33siswa (100%).Pada akhir PTK motivasi belajar siswa dalam kriteria tinggi (84,48). Hasil penelitian membuktikan penggunaan Model Pembelajaran Cooperative learning Tipe Jigsawmeningkatkan motivasi dan prestasi belajar matematika materi bangun datar segi empatsiswa kelas VII semester II MTsN Yogyakarta I Mlati Sleman tahun pelajaran 2015/2016 dan dapat dijadikan prediktor yang baik. Oleh karena itu dalam pembelajaran matematika dapat diterapkan Model Pembelajaran Cooperative learning Tipe Jigsaw untuk meningkatkan motivasi dan prestasi materi bangun datar segi empat.Â Implementation of cooperative learning type jigsaw learning model in the framework of increasing motivations of achievement of math statements students of class VII MTsN Yogyakarta its lesson 2015/2016 AbstractLearning Model Cooperative Learning Type Jigsawdi class VII MTsN Yogyakarta I Mlati Sleman 2015/2016 SD lesson year aims to improve motivation and achievement of learning mathematics material wake rectangular flat. Classroom Action Research is done by the researcher as a classroom teacher and grade 9 mathematics teacher as an observer. The research was conducted in two cycles, the subjects of this study were the second grade students of second semester of MTsN Yogyakarta I Mlati Sleman 2015/2016 academic year amounted to 33 students. Data analysis techniques used comparative analysis. From the percentage is described towards the tendency of teacher action and reactions and student learning outcomes.Prestasi learning before the class action an average of 69.58 individual completeness as much as 22 students (66.7% ).After class action on the cycleI average score of 73.75 with mastery Individual students (84.84%), cycle II average score reached 77.33 with individual completeness 33 students (100%) At the end of TOD the students' learning motivation in high criterion (84,48) The research results proved the use of Learning Model Cooperative Learning Type Jigsawmend the motivation and achievement of learning mathematics of building the rectangular building of class VII second semester of MTsN Yogyakarta I Mlati Sleman of academic year 2015/2016 and can be a good predictor. Therefore, in the learning of mathematics can be applied Learning Model Cooperative learning Type Jigsaw to improve motivation and achievement of building of rectangular flat.